Overshadowed by the Younger Brother: The Art of Ambrosius Holbein - Volosova, Daria V. (Actual Problems of Theory and History of Art, 2019)
The present article is devoted to studying the art of Ambrosius Holbein — the elder brother of Hans Holbein the Younger. He died at the age of 25 leaving behind only a small body of works and he always remained in the shadow of his famous brother. The only monograph dedicated to Ambrosius Holbein was written more than 100 years ago. Generally, the artist is simply treated as the brother of the famous artist, Hans Holbein the Younger. The paper deals with attributed works of Ambrosius Holbein: graphic works will be presented, including the book graphics, wall-paintings and paintings. The “Portrait of a Young Man” from the Hermitage collection is the only work convincingly attributed to him. The author pays attention to the problem of identification of the young man depicted in this portrait. The paper shows that the art of Ambrosius Holbein, as well as his life, requires a far deeper study.